Application of refined nursing model based on Watson’s theory of human caring for patients undergoing electronic bronchoscopy (基于Watson人性照护理论的精细化护理模式在电子支气管镜检查中的应用) - LI Lin (李琳); LIU Yinshuang (刘银双); FENG Wenying (冯文英); ZHAO Jing (赵静) (中西医结合护理)
Objective To explore the application effect of refined nursing interventions based on Watson’s theory of human caring for patients undergoing electronic bronchoscopy. Methods Totally48 patients who underwent electronic bronchoscopy between April 2022 to October 2022 were selected as the control group, and received routine nursing during treatment. Another 50 patients who underwent electronic bronchoscopy from November 2022 to April 2023 were selected as the observation group, and refined nursing mode based on Watson’s theory of human caring was given on the basis of routine nursing. The humanistic care ability of nurses, scores of Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) before and after examination, the time of microscopic examination and the satisfaction of patients with examination were compared between the two groups. Results After implementing the refined nursing model based on Watson’s theory of human caring, the humanistic care ability of nurses was improved, and the difference was statistically significant (P<0. 01). The scores of SAS and SDS and the time of microscopic examination in the observation group were significantly lower than those in the control group (P<0. 01), and the satisfaction of patients in the observation group was significantly higher than that in the control group (P<0. 01). Conclusion The refined nursing model based on Watson’s theory of human caring can effectively relieve the anxiety and depression of patients undergoing bronchoscopy, improve their adherence to endoscopic treatment. (目的 探讨基于Watson 人性照护理论的精细化护理干预模式在电子支气管镜检查中的应用效果。方法 选取2022年4月—10月收治的48例行电子支气管镜检查的患者为对照组, 给予常规护理措施; 2022年11月—2023年4月收治的50例行电子支气管镜检查的患者为观察组, 在常规护理基础上给予基于Watson人性照护理论的精细化护理模式。评价护士的人文关怀能力, 对比两组患者焦虑自评量表(SAS)、抑郁自评量表(SDS)评分, 以及镜检时间、患者对检查的满意度。结果 实施基于Watson人性照护理论的精细化护理模式后, 护士人文关怀能力得到提升(P＜0. 01); 观察组SAS、SDS评分及镜检时间均低于对照组, 患者对检查的满意度高于对照组, 差异有统计学意义(P＜0. 01)。结论 基于Watson 人性照护理论的精细化护理模式能有效改善支气管镜检查患者的焦虑、抑郁等不良情绪, 提升患者检查配合度。)